Medieval manuscripts in transition : tradition and creative recycling - Claassens, Geert H. M.; Verbeke, Werner (Mediaevalia Lovaniensia, 2006)
Manuscripts constitute the source material par excellence for diverse academic disciplines. Art historians, philologists, historians, theologians, philosophers, book historians and even jurists encounter one another around the codex. The fact that such an encounter can be extremely fertile was demonstrated, during an international congress in Brussels on November 5-9, 2002.A record of the discussions can be found in this volume of the Mediaevalia Lovaniensia. The editors selected those lectures that focused on the historical, literary-historical, philosophical and theological aspects of the co.